Firms' Voluntary Recognition of Stock‐Based Compensation Expense - ABOODY, DAVID; E. BARTH, MARY; KASZNIK, RON (Journal of Accounting Research, 2004)
ABSTRACT We investigate factors associated with firms' decisions in 2002 and early 2003 to recognize stock‐based compensation expense under Statement of Financial Accounting Standards (SFAS) No. 123. We find that the likelihood of SFAS 123 expense recognition is significantly related to the extent of the firm's participation in capital markets, the private incentives of top management and members of the board of directors, the level of information asymmetry, and political costs. Although recognizing firms have significantly smaller SFAS 123 expense, we find no significant incremental relation between recognition likelihood and SFAS 123 expense magnitude after controlling for other factors that we expect explain the recognition decision. We also find positive and significant announcement returns for earlier announcing firms, particularly those stating that increased earnings transparency motivates their decision.